Latihan Berjalan Meningkatkan Kekuatan Otot dan Keseimbangan pada Lansia dengan Risiko Jatuh: A Scoping Review - Sari, Citra Windani Mambang; Rahma, Valenty Rafaustine; Jatiningtyas, Kurnia; Salsabella, Edellweisse Silvia; Dinan, Nur Azmina; Masroorianissa, Aulia Fauzia; Hidayatulloh, Parwiin Salma Zaenab (JURNAL CITRA KEPERAWATAN, 2023)
Introduction: Falling is one of the most important symptoms and the main etiology of morbidity and mortality for the elderly aged 65 years. In the elderly who are at risk of falling, stretching (flexibility) and balance exercises are recommended in the physical activity program. This literature review aims to identify whether walking exercises are effective in reducing the risk of falling in the elderly and to find out whether walking exercises can train muscles and balance in the elderly.Method: The method used is scoping review. Literature searches were obtained from several databases of Cinahl Plus, Pubmed, and Springer by applying the keywords "elderly, walking exercise, physical mobility improvement" which were developed using the PICO method. Six articles were obtained for analysis according to PRISMA guidelines in the process by setting inclusion criteria.Results: The results of the scoping review showed that all 6 articles had elderly respondents (n= 242) consisting of healthy elderly (n=186) and elderly with a history of illness (n=52). Walking exercises applied to the elderly have proven effective in increasing muscle strength and balance in both healthy elderly and elderly with a history of illness.Conclusion: Walking exercise is effective as a non-pharmacological intervention in the elderly with a risk of falling. Interventions applied in several experiments have been shown to be able to train muscle strength and balance in the elderly